Efecto tiempo-temperatura de tostado del cacao fino de aroma en sus características fisicoquímicas y organolépticas - Álava Moreira, Ladys Maribel (2016)
With this research, it was determined the effect of roasting time-temperature of Cocoa of fine Aroma for the Valley Fortress Corporation, in Calceta-Manabi- Ecuador; with a completely random design (DCA) of two factors in study: Factor A: toasting time with levels of 35, 45, 50 minutes, and Factor B temperature toasting, with levels of 115, 125, 130 degrees Celsius, applying 2 replicas, resulting in 27 experimental units with size of 2 kg, of dry cacao. The variables evaluated were: physicochemical before roasting (head and humidity), after roasting the beans (ash and grease), organoleptic basic tastes (sour, acidity and astringency), flavors (floral, fruity, nutty and caramel), defects (green and rust), smell (floral and fruity) and texture (soft and doughy). In the analysis of moisture, head, fat and ash was found statistically non significant among factors and their interactions. The values of moisture and head exceeded the norm NTE INEN 176, fat and ash values are within the standard INEN 623. At organoleptic, related attributes, specific flavor stood out cocoa, floral, fruity flavors; the best treatment was T3 and with less value in the same attributes T8 treatment; in basic tastes the bitter attribute the highest percentage was T8 treatment and the T3 the lowest. Finding no defects in the analyzed treatments. In smell, stands out the floral, still T7 with higher value attributed, finding no significant difference in texture between the factors.